Pitch Syntax Violations Are Linked to Greater Skin Conductance Changes, Relative to Timbral Violations – The Predictive Role of the Reward System in Perspective of Cortico–subcortical Loops - Gorzelańczyk, Edward J.; Podlipniak, Piotr; Walecki, Piotr; Karpiński, Maciej; Tarnowska, Emilia (Frontiers in Psychology, 2017)
According to contemporary opinion emotional reactions to syntactic violations are due to surprise as a result of the general mechanism of prediction. The classic view is that, the processing of musical syntax can be explained by activity of the cerebral cortex. However, some recent studies have indicated that subcortical brain structures, including those related to the processing of emotions, are also important during the processing of syntax. In order to check whether emotional reactions play a role in the processing of pitch syntax or are only the result of the general mechanism of prediction, the comparison of skin conductance levels reacting to three types of melodies were recorded. In this study, 28 subjects listened to three types of short melodies prepared in Musical Instrument Digital Interface Standard files (MIDI) – tonally correct, tonally violated (with one out-of-key – i.e. of high information content), and tonally correct but with one note played in a different timbre. The BioSemi ActiveTwo with two passive Nihon Kohden electrodes was used. Skin conductance levels were positively correlated with the presented stimuli (timbral changes and tonal violations). Although changes in skin conductance levels were also observed in response to the change in timbre, the reactions to tonal violations were significantly stronger. Therefore, despite the fact that timbral change is at least as equally unexpected as an out-of-key note, the processing of pitch syntax mainly generates increased activation of the sympathetic part of the autonomic nervous system. These results suggest that the cortico-subcortical loops (especially the anterior cingulate - limbic loop) may play an important role in the processing of musical syntax.